OptoSkin: Novel LIDAR Touch Sensors for Detection of Touch and Pressure within Wave guides - Garcia Pueyo, Jorge; Bacher, Emmanuel; Zore, Ales; Stopar, Julija; Kamnik, Roman; Grube, Jurgis; Kemere, Meldra; Butikova, Jelena; Bundulis, Arturs; Ogurcovs, Andrejs; Aulika, Ilze; Muñoz, Adolfo; et al. (Jornada de Jóvenes Investigadores del I3A, 2025)
We propose OptoSkin, a novel type of sensor for touch and pressure detection. It is based on direct Time-of-Flight (dToF) measurements of light propagated within wave guides due to Total Internal Reflection (TIR). It shows great potential for applications like robotic sensor skins for being compact, cheap and easy to fabricate.